Genetic studies of Polish migraine patients: screening for causative mutations in four migraine-associated genes. Issue 1 (December 2016) - Domitrz, Izabela; Kosiorek, Michalina; Żekanowski, Cezary; Kamińska, Anna
Abstract Background and aim Migraine is the most common neurological disorder, affecting approximately 12 % of the adult population worldwide, caused by both environmental and genetic factors. Three causative genes have been identified in familial hemiplegic migraine (FHM) families:CACNA1A, ATP1A2, andSCNA1A . Recently, several mutations inKCNK18 have also been found as causative factors in migraine development. The aim of our study was to identify the genetic background of migraine in the Polish population. Material and methods Sixty patients with migraine without aura (MO) or with different types of migraine with aura (MA), including sporadic hemiplegic, familial hemiplegic, and probable familial hemiplegic, were screened for mutations in the four genes previously linked with different types of migraine (ATP1A2, CACNA1A, SCN1A, andKCNK18 ). Results Two missense mutations were found. One novel mutation inSCN1A, encoding α subunit of sodium channel, causing amino acid change M1500V localized to a region encoding inactivation loop between transmembrane domains III and IV of the channel, was detected in a female FHM patient. The M1500V mutation was absent in a group of 62 controls, as well as in the ExAC database. The second, already known missense mutation S231P inKCNK18 was found in a female MA patient. Additionally, a novel intronic polymorphism possibly affecting alternative splicing ofSCN1A, at chr2:16685249, g.77659T>C, and c.4581+32A>G, located between exons 24 and 25, in a region encoding the inactivation loop of the sodium channel was found in a female MO patient. No mutations inATP1A2 orCACNA1A were found in the study group. Conclusions The presence ofSCN1A mutations and absence of mutations inATP1A2 or CACNA1A suggest that the Polish patients represent FHM type 3. On the other hand, the presence ofKCNK18 mutation indicated another FHM subtype. It could be speculated that contrary to other European populations, the genetic basis of migraine in the Polish population involves mutations in genes not included in the study. Next-generation sequencing methods should be implemented to identify other migraine-associated variants.